Effect of block geometry on the estimation of low volumetric block proportions: A tunneling-based computer bimrock model - Zixin Zhao; Guolong Zhu; Xingliang Peng; Fawu Wang (Underground Space)
Bimrocks have a block matrix structure that affects their characteristic complex geometric features and widely varying engineering properties. Volumetric block proportion (VBP) significantly affects the strength, extent of the plastic zone, and failure mode of bimrocks. VBP is an essential parameter for evaluating bimrock mechanical properties. However, current unadjusted VBP estimations may have large errors that can exceed 100%. Obtaining more accurate VBP estimates at engineering sites is an ongoing problem that needs more attention. In this study, a tunneling-based bimrock model was constructed. The blocks were ellipsoidal, and their geometric features were designed to be changeable. Based on this model, the influence of bimrock block geometry features on the estimation of the VBP was explored. To reduce the estimation error of the VBP in the tunnel, correction factors corresponding to different geometrical features were proposed. The results of this study can help in estimating VBP more accurately in the field. The findings can also provide useful information for the tunnel construction.